2019
DOI: 10.1002/jts.22386
|View full text |Cite
|
Sign up to set email alerts
|

Impact Statement Coding of Self‐Related Thought in Women With Posttraumatic Stress Disorder

Abstract: Clinical and empirical studies have documented significant alterations in self-related thought in posttraumatic stress disorder (PTSD). To our knowledge, however, few studies have examined self-referential cognition by analyzing survivors' written impact statements in individuals whose PTSD is due to interpersonal trauma. In the current study, we performed a linguistic analysis of impact statements (i.e., descriptions of how the trauma has affected the survivors' views of themselves, others, and the world) col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(83 reference statements)
1
2
0
Order By: Relevance
“…Here, we found that improvements in both arousal and reactivity symptoms are associated with increased hippocampal-DMN connectivity in a sample of young women exposed to sexual trauma. These results are consistent with previous research linking PTSD-related alterations in self-referential processing to arousal symptoms in women with PTSD secondary to interpersonal trauma ( Philippi et al, 2019 ). Previous research has found unique neural alterations linked to different types of trauma in childhood ( Teicher et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we found that improvements in both arousal and reactivity symptoms are associated with increased hippocampal-DMN connectivity in a sample of young women exposed to sexual trauma. These results are consistent with previous research linking PTSD-related alterations in self-referential processing to arousal symptoms in women with PTSD secondary to interpersonal trauma ( Philippi et al, 2019 ). Previous research has found unique neural alterations linked to different types of trauma in childhood ( Teicher et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…The hippocampus has long been a key region of interest for PTSD research, due to the role it plays in memory, fear learning, and fear extinction, functions that are perturbed by PTSD ( Joshi et al, 2020 ). Furthermore, connectivity within the DMN, including the hippocampus, is associated with autobiographical memory and self-referential thought ( Frewen et al, 2011 ; Menon, 2011 ), processes that are also altered by PTSD ( Frewen et al, 2011 ; Philippi et al, 2019 ). Here, we found that improvements in both arousal and reactivity symptoms are associated with increased hippocampal-DMN connectivity in a sample of young women exposed to sexual trauma.…”
Section: Discussionmentioning
confidence: 99%
“…“… fly”). We followed modern research practice and evaluated the SFSC based on the count of “egocentric” and the “egocentric and negative” responses [ 12 , 61 , 62 ]. We divided their sum by the number of raters and the number of SFSC items to get a ratio of self-focus that is as unbiased as possible by the coding variability of an individual rater.…”
Section: Methodsmentioning
confidence: 99%